ANALISIS DEBIT BANJIR SUNGAI NAE BIMA DENGAN HSS (HIDROGRAF SATUAN SINTETIS) SNYDER - SABRINI AL QAUTSAR; MUHAMAD YAMIN; AMINULLAH AMINULLAH (SOSIAL SAINS DAN TEKNOLOGI, 2023)
The purpose of this study was to analyze the magnitude of the design flood discharge at various return periods of 5, 10, 20, 25, 50, 100 years, and to analyze the peak discharge, peak time and bottom time on the Nae River using the Snyder Synthetic Unit Hydrograph. This research method is a quantitative study with flood analysis designed by the Snyder Synthetic Unit Hydrograph. The results of the calculation of the design flood discharge with a return period of 5 years is 62,154 m3, a 10-year return period is 124,419 m3, a 20-year return period is 249,389 m3, a 25-year return period is 311,929 m3, a 50-year return period is 623,913 m3, a 100-year return period year of 1247.881 m3. The results of calculations using the Snyder HSS method are obtained, the peak time (Tp) is 7.59 hours, the peak discharge (Qp) is 4.131 m3, the base time (Tb) is 26.831 hours